Effectiveness of The Team Games Tournament (TGT) Learning Model Using Wordwall on Mathematics Learning Outcomes on Plane Shapes at Smp Negeri 9 Kota Sorong - Falni, Falni; Musa’ad, Faida; Rusani, Irna; Fathurrahman, Muhammad; Trisnawati, Nika Fetria; Fernayanan, Riyanti; Djoroho, Theresia G (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model assisted by a word wall on the mathematics learning outcomes of eighth-grade students at SMP Negeri 9, Sorong City. The method used was a pre-experimental one with a One Group Pretest-Posttest design. The sample consisted of 25 students, and the research instruments in the form of pretest and posttest. Data analysis used the Shapiro-Wilk test, the Wilcoxon Signed Ranks Test, and the N-Gain test. The results showed a significant difference between pretest and posttest scores (p = 0.000 < 0.05) and an average N-Gain of 0.63 (moderate category). Learning with TGT assisted by a word wall has been proven to effectively improve students' conceptual understanding and learning motivation